Impacts on Thrombus and Chordae Willisii During Mechanical Thrombectomy in the Superior Sagittal Sinus - Ye, Yuanliang; Ding, Jiuyang; Liu, Shoutang; Huang, Shaoming; Li, Zhu; Yang, Jianqing; Huang, Jiang (Frontiers in Neurology, 2021)
The anatomical structures of superior sagittal sinus (SSS) were usually damaged during mechanical thrombectomy (MT), and MT procedure could lead to new thrombosis in the sinuses. However, the mechanism remains unclear. We aimed to investigate the risks of embolism and assess the damage to chordae willisii (CW) associated MT using a stent passing across the thrombus. A contrast-enhanced in vitro model was used to mimick MT in the SSS. The thrombus was removed with a stent. The emboli generated during the procedure were collected and measured. The residual thrombus area after the MT was measured by J Image software. The damage of CW was evaluated by an endoscope. Three procedural experiments were carried out on each cadaveric sample. The average numbers of visible emboli particles in experiments 1, 2, and 3 were 11.17±2.17, 9.00±2.07, and 5.00±2.96, respectively. The number of large size particles produced by experiment 1 was significantly higher than that of other experiments. The thrombus area measured after experiment 3 was larger than that of experiments 1 and 2. The number of minor damage cases to CW were 55 (90.16%) and there were 6 serious damage cases (9.84%). The use of stent resulted in no significant increase in damage to CW after the three experimental procedures. Large amount of thrombi particles were produced during MT and multiple MT procedures on the same sample can increase residual thrombus area. Moreover, the stent caused minor damages to the CW in SSS.